(untitled) (Nepalese Journal of Radiology, 2013)
The thalassemias are a heterogenous group of inherited disorders of hemoglobin (Hb) synthesis characterized by a lack of or decreased /defective synthesis of globin chains. The name Mediterranean anemia, which Whipple introduced, is misleading because the condition can be found in any part of the world. In ?-thalassemia, ?-globin chain synthesis is reduced, whereas in ?-thalassemia, ?-globin chain synthesis is defective. Their clinical severity varies widely, ranging from asymptomatic forms to severe or even fatal entities. Like most anemias, erythropoietin production and erythropoiesis is increased in thalassemia causing erythroid marrow hyperplasia as well as extramedullary haematopoiesis which is a common compensatory mechanism for chronic anemia found in patients with hemoglobinopathies such as thalassemia, sickle cell anemia, and hereditary spherocytosis. These patients are usually asymptomatic. Extramedullary hematopoiesis (EMH) usually manifests in the liver, spleen, kidneys and as paravertebral masses. Extramedullary hematopoietic tissue occurring within the spinal canal and causing cord compression is an unusual but well-described entity. Total surgical excision is usually not feasible because of the diffuse spread of extramedullary hematopoietic tissue and the possibility of recurrence, but acute neurological impairment does require emergency surgery. Extramedullary hematopoiesis is radiosensitive so radiation therapy is widely accepted as a very effective mode of therapy. Repeated blood transfusion and cytostatic agents are also recommended for treatment.We report a case of a 35-year-old man with underlying beta thalassemia intermedia who developed pain in lower back and progressive paresthesia and weakness of both lower limbs due to multifocal extramedullary epidural hematopoietic tissue occurring within the spinal canal with compression over the cord. Nepalese Journal of Radiology; Vol. 2; Issue 2; July-Dec. 2012; 81-85 DOI: http://dx.doi.org/10.3126/njr.v2i2.7692